2013
DOI: 10.1007/s10238-013-0266-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapy for insulin-dependent diabetes mellitus: infusion of in vitro-generated insulin-secreting cells

Abstract: Insulin-dependent diabetes mellitus (IDDM) is a metabolic disease usually resulting from autoimmune-mediated β-cell destruction requiring lifetime exogenous insulin replacement. Mesenchymal stem cells (MSC) hold promising therapy. We present our experience of treating IDDM with co-infusion of in vitro autologous adipose tissue-derived MSC-differentiated insulin-secreting cells (ISC) with hematopoietic stem cells (HSC). This was an Institutional Review Board approved prospective non-randomized open-labeled clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…For example, MSCs can differentiate into insulin-producing cells, suggesting MSCs as a source of transplantation material in the treatment of diabetes, [72][73][74] while other studies demonstrated the angiogenic and anti-inflammatory potential of MSCs in supporting islet transplantation. 75,76 Furthermore, Dave et al 77 reported a clinical trial showing that co-infusion of in vitro-generated insulin-producing cells differentiated from autologous adipose-derived MSCs and bone marrow-derived hematopoietic stem cells into the portal circulation, thymus, and subcutaneous tissue increased serum C-peptide levels and improved glycosylated hemoglobin levels. Significant progress has thus been made in the field of MSC and diabetes, and further research is warranted to realize the clinical potential of MSC adipogenesis in this area.…”
Section: Mscs and The Comorbidities Of Obesitymentioning
confidence: 99%
“…For example, MSCs can differentiate into insulin-producing cells, suggesting MSCs as a source of transplantation material in the treatment of diabetes, [72][73][74] while other studies demonstrated the angiogenic and anti-inflammatory potential of MSCs in supporting islet transplantation. 75,76 Furthermore, Dave et al 77 reported a clinical trial showing that co-infusion of in vitro-generated insulin-producing cells differentiated from autologous adipose-derived MSCs and bone marrow-derived hematopoietic stem cells into the portal circulation, thymus, and subcutaneous tissue increased serum C-peptide levels and improved glycosylated hemoglobin levels. Significant progress has thus been made in the field of MSC and diabetes, and further research is warranted to realize the clinical potential of MSC adipogenesis in this area.…”
Section: Mscs and The Comorbidities Of Obesitymentioning
confidence: 99%
“…In patients with type 1 diabetes, co-transplantation of ASC-derived insulin-secreting islets with hematopoietic stem cells decreased exogenous insulin requirement, increased c-peptide levels, and prevented ketoacidosis [ 26 ]. In another clinical trial in the same patient population, transplantation of ASC-derived insulin + cells improved patients’ HB1Ac levels, and decreased serum GAD antibody, without causing adverse effects [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MSC are immune-privileged because they express very low levels of major histocompatibility complex (MHC) class I and no MHC class II which normally prevents or strongly reduces immune responses [172,173]. In clinical use since 1995 [56], MSC are considered clinically safe [106] and both administration of autologous and also allogenic MHC-mismatched MSC is generally well tolerated and clinically effective [174][175][176].…”
Section: Msc In Clinical Trialsmentioning
confidence: 99%